Developing Indonesian Speaking Skills Using Language Game Learning Method for Elementary Students in Labuhan Batu Regency - Ali, Asmuri; Sutikno; Kartolo, Rahmat; Harianti II (International Journal of English and Applied Linguistics (IJEAL), 2025)
Indonesian-speaking skills of fourth-grade students are low because of a lack of confidence, fluency, and minimal active participation in conventional oral learning. This study also aims to determine the effectiveness of using language game learning methods in improving students' speaking skills and activity. The research method uses Kemmis and McTaggart’s Classroom Action Research (CAR) model, which is implemented in two cycles, where each cycle consists of four stages. The subjects are 30 fourth-grade students. Data collection instruments include a performance test (oral assessment) and student activity observation sheets. The criteria for the success of the action are determined if the percentage of classical completeness reaches at least 80%. The results show that there is a consistent and significant increase. The average score of students’ speaking skills in the pre-action stage only reaches 55.00, with a very low percentage of classical completeness. After the implementation of language games in Cycle I, the average score increases to 72.50 (65% completeness). Through corrective actions in Cycle II, the average score increases again to 85.00, and the classical completion percentage reaches 90%. This improvement is also accompanied by increasing students’ activity and confidence in speaking in class. Based on these results, this study concludes that the language game learning method is effective and successful in developing Indonesian speaking skills. This method has been proven to create a fun, interactive learning environment and motivate students to dare to speak, so the action hypothesis is accepted.